EFFECTS OF INGUINAL HERNIA REPAIR ON MALE FERTILITY - Muhammad Rehman Gulzar; Abid Rasheed; Muhammad Akram (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To determine the frequency of male infertility in patients undergoing inguinal hernia repair. SUMMARY BACKGROUND DATA: In fertility after inguinal hernia repair is not a documented complication so no definite background data is available. SETTING: Surgical floor, Allied Hospital, Faisalabad. METHODS: Patients undergoing unilateral, primary inguinal hernia repair electively with the Lichtenstein technique were included in study after determining their preoperative fertility status in terms of sperm motility and sperm concentrations which were again checked six and twelve weeks post operatively. Patients with obstructed, strangulated or recurrent hernia, patients with immunosuppressive disease or a debilitating disease like chronic liver, renal or cardiac impairment were excluded. Age, side of hernia, type, size, reducibility and operative findings were recorded. Male infertility was defined according to WHO criteria. Semen analysis was carried out on the day of operation and 6 and 12 weeks post operatively. Result were recorded and analyzed. RESULTS: Between April 25th 2011 and October 2011, a total of 219 patients were included in study. None of the patients developed any urinary tract infection, trauma to urinary tract and significant wound infection post operatively. Out of219 patients 155 had right sided and 64 patients had left sided hernias, 60 were direct and 159 were indirect clinically. 119 patients had complete and 100 patients had incomplete hernias, 107 hernias were reducable and 112 were Irreducible. When operated 14 patients had direct and indirect both hernias. Hernial sac dissection was easy in 155 cases and was adherent in 114. Two scrotal hematomas, 3 cases of wound seroma formation and 3 cases of urinary retention were noticed. CONCLUSIONS: We conclude that none of the patients developed infertility till 12 weeks post operatively.